2001
DOI: 10.1002/1096-9861(20010305)431:2<129::aid-cne1060>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Amygdalar activation alters the hippocampal GABA system: ?Partial? modelling for postmortem changes in schizophrenia

Abstract: Abnormalities in amygdala and hippocampus have been shown to coexist in schizophrenia (SZ). In the hippocampus, compelling evidence suggests that a disruption of GABA neurotransmission is present mainly in sectors CA4, CA3, and CA2. The amygdala sends important inputs to the hippocampus and is also believed to have a defective GABA system in schizophrenia. To explore the possibility that changes in the hippocampal GABAergic system could be related to an increased inflow of activity originating in the amygdala,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 85 publications
4
47
0
Order By: Relevance
“…Therefore, a failure of the mPFC to regulate stress in the MAM-treated rat or in the prodromal stage of schizophrenia could contribute to pathological changes in the hippocampus observed in this disorder. It has been shown that activation of the amygdala, which occurs during stress, will lead to parvalbumin interneuron loss in the hippocampus (Berretta et al, 2001) and loss of hippocampal parvalbumin interneurons is proposed to lead to the DA hyper-responsivity in the MAM model (Lodge and Grace, 2007). Thus, a hypersensitivity to stress potentially secondary to decreased mPFC function could initiate a cascade of events during juvenile/adolescent stages to lead to hippocampal dysfunction and the emergence of the schizophrenia-like phenotype observed in the MAM model (Grace, 2004;Thompson et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a failure of the mPFC to regulate stress in the MAM-treated rat or in the prodromal stage of schizophrenia could contribute to pathological changes in the hippocampus observed in this disorder. It has been shown that activation of the amygdala, which occurs during stress, will lead to parvalbumin interneuron loss in the hippocampus (Berretta et al, 2001) and loss of hippocampal parvalbumin interneurons is proposed to lead to the DA hyper-responsivity in the MAM model (Lodge and Grace, 2007). Thus, a hypersensitivity to stress potentially secondary to decreased mPFC function could initiate a cascade of events during juvenile/adolescent stages to lead to hippocampal dysfunction and the emergence of the schizophrenia-like phenotype observed in the MAM model (Grace, 2004;Thompson et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, cortex and hippocampus are regions strongly implicated in the pathophysiology of schizophrenia. [35][36][37][38] It was previously reported that density of neurons can be significantly reduced in certain layers of the cortex of schizophrenics. For example, schizophrenic subjects showed a significant decrease in density of nonpyramidal neurons in layer II and pyramidal neurons in layer IV of the anterior cingulated cortex.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the burst-spiking horizontal and bitufted cells of layers I and II receive on their dendrites both excitatory axon terminal projections from thalamus and cortico-cortical pyramidal neurons 53 and massive excitatory axon terminal projections from the basolateral nucleus of the amygdala. [58][59][60][61] It has been suggested that amygdalo-cortical or cortico-cortical excitatory inputs to layer I and II cortical GABAergic interneurons may help to suppress information arriving at distal pyramidal neuron dendrites and den-dritic spines directly from MD afferent synapses. 52,53 Therefore, as proposed by Benes,58 and based on the data reported in this study, one can hypothesize that the selective decrease in GABAergic inhibitory function observed in layer I of SZP PFC may be the consequence of a specific disorganization of the complex neuronal afferent network reaching GABAergic interneurons of layers I and II from the amygdala or other cortico-limbic regions.…”
Section: Dnmt1 Mrna Overexpression In Pfc Of Szp Is Restricted To a Smentioning
confidence: 99%
“…52,53 Therefore, as proposed by Benes,58 and based on the data reported in this study, one can hypothesize that the selective decrease in GABAergic inhibitory function observed in layer I of SZP PFC may be the consequence of a specific disorganization of the complex neuronal afferent network reaching GABAergic interneurons of layers I and II from the amygdala or other cortico-limbic regions. [58][59][60][61] In schizophrenia, the disorganization of the MD afferent network reaching the GABAergic interneurons of the deeper cortical layers may be less pronounced or localized to only a small subset of neurons such as the chandelier neurons, which have been shown to be dysfunctional in SZP. 23 Is DNMT1 overexpression in layer I cortical GABAergic neurons causally related to the decrease of GAD 67 and reelin?…”
Section: Dnmt1 Mrna Overexpression In Pfc Of Szp Is Restricted To a Smentioning
confidence: 99%